Change Stages of Inter-dental Cleaning Behavior Based on Transtheoretical Model among Pre-university Students in Yazd, Iran - A Fallahi; M Morovati Sharifabad (Tehran University of Medical Sciences, 2009)
Background and Aim: Teeth-mouth diseases include a cost between 10-5% of the total of cost of health care and have the damaging effects on childhood and in adult. Transtheoretical Model shows change of behavior dynamically. The purpose of this study was to determine Stages of change of inter-dental cleaning behavior based on Transtheoretical Model in male and female students in Yazd, Iran.Results: In this study 54.8% female and 45.2% males participated with mean age of 17.35 ±.55 years. %49.6(59student) of students were in pre contemplation stage. Other participants were 5.3 % (19) in contemplation, 24.1 % (87) in preparation, 6.8% (31) in action and 12.5% (5) in maintenance stage. There was a positive significant relationship among stages of change with self-efficacy (r=0.33) and perceived benefits (r=0.19). Also a negative significant relation between stages of change and perceived barriers (r= -0.19) was oberved. Constructs of the model were statically significant predictors of stages of change and accounted for 0.15% of the variation that self efficacy was most important predictors (β=0.212).Materials and Methods: This cross-sectional study was performed on pre-university 361 students in 8 schools cluster sampling. The instrument for collecting the information were questionnaires consisting of demographic characteristics, self-efficacy questions, decisional balance (perceived advantages and perceived obstacles) and stages of change of interdental cheaning behavior. Reliability and validity of questionnaires was confirmed. The data collected by interview and analyzed by SPSS.Discussion and Conclusion : In this study, most of students were in pre contemplation stage. They will be probably exposed to dental caries. Not only Trans-theoretical Model can be a model to determine strategies to each stage of change of teeth-mouth self - care Behavior but can also be used in educational interventions.